Oxidative balance and survival in osteoporosis: how antioxidant diets and lifestyles reduce mortality risk - Ding, Ziyao; Qi, Haixu; Li, Wenbo; Chen, Changchang; Li, Youwei; Sun, Jun; Sun, Maji; Feng, Shuo; Yuan, Feng (Frontiers in Nutrition, 2025)
BackgroundOsteoporosis (OP) is a global health issue characterized by reduced bone mineral density (BMD) and an elevated risk of fractures. Oxidative stress is implicated in OP pathogenesis, and antioxidant diets and lifestyles may mitigate these effects. This research aims to investigate the correlation between oxidative balance score (OBS) and all-cause mortality in individuals diagnosed with OP.MethodsThis study is based on data from the National Health and Nutrition Examination Survey (NHANES, 2005–2018), which covers 776 OP patients aged 50 or older. OBS was computed using dietary and lifestyle factors, and divided into two categories: dietary oxidative balance score (DOBS) and lifestyle oxidative balance score (LOBS). Participants were grouped into tertiles based on OBS values.ResultsKaplan–Meier survival analysis revealed significantly higher survival in the high OBS group compared to the low OBS group (p = 0.0032). Consistently, weighted Cox proportional hazards models demonstrated a negative association between OBS and all-cause mortality [HR = 0.96, 95% CI (0.94, 0.99), p = 0.0036].ConclusionOBS is inversely correlated with all-cause mortality among OP patients, underscoring the critical role of antioxidant-rich diets and lifestyle modifications in OP prevention and treatment strategies. Incorporating OBS into clinical practice may help identify high-risk individuals and guide targeted interventions to reduce mortality risk.